Clinicopathological evaluation of postmenopausal bleeding - Agrawal, Manjusha; Kotpalliwar, Monika K.; Kotpalliwar, Swadha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Seventy percent of cases of postmenopausal bleeding have an innocent or harmless cause of bleeding but 30% of them are associated with malignancy. Hence it requires a thorough evaluation clinically and pathologically. As a considerable number of patients complaining of postmenopausal bleeding are reporting, the current study was undertaken to find out the incidence of the postmenopausal bleeding and the causes responsible for it. Methods: A hospital based cross sectional study was performed on women with the history of post-menopausal bleeding. Patients with premature menopause whether surgical or natural (age <40 years), patients having bleeding from urethra or rectum and patients on hormone replacement therapy and anticoagulation therapy were excluded from the study. After the detailed history and a thorough examination, all the patients were subjected to USG. In cases, wherever required colposcopy, biopsy, laparotomy or hysterectomy was performed and were correlated histopathologically. Results: Incidence of 11/1000 patients was found. The mean age of menopause was 46.99 years and mean duration was 7.20 years. Clinically the most common cause was Ca endometrium (26%), whereas histopathologically atrophy (34.61%) was the commonest cause. 61% had benign cause whereas 39% had malignant cause for post-menopausal bleeding. Conclusions: From the study, it is revealed that the incidence of postmenopausal bleeding decreases with increase in the age of patient as well as with the increasing duration of the menopause. Scanty endometrium is associated normal histopathology of endometrium and hence patients of postmenopausal bleeding with endometrial thickness > 5 mm should be thoroughly investigated, treated and followed up meticulously.